A feasibility study on the use of water hyacinth in eco-bag production - Maricon R. Angco, Khylle Xavier G. Bautista, Chaerra Fei D. Dungka, Riz Mari Y. Flores, Gian Mae C. Manuel, Marth Louise R. Mora, Matthew Freddy A. Racadio, Johanna M. Reyes, Blesserce Joice L. Ruzol 4 0 16; 5
Background of the Study Ilog Pasig is a 27-km river connecting Manila Bay in the west and Laguna de Bay in the east. Its diversified streams link the cities of Makati, Mandaluyong, Manila, Pasig, Taguig, and the municipality of Taytay, Rizal. As the river was declared biologically dead in the 1990s, the landscape has changed considerably due to developments and environmental changes. The fast urbanization and industrialization of the surrounding cities had degraded the river's beauty and great history. Before, it was used as the main channel for international trade during the colonial period. Water hyacinth (Eichhornia crassipes) is a free-floating, perennial, and invasive aquatic plant growing on rivers, lakes, and other bodies of water that can expand to a height of eight inches to a meter. It has glossy green leaves, and some of its varieties have large blue to purple flowers. As a fast-growing plant, its population can be doubled every six to eighteen days. A single plant may generate up to five thousand seeds on its own, which explains it can multiply in a vast mass within a short time due to constant seed dispersal through wind, birds, water, and other channels. The excessive growth of water hyacinth blocks waterway flow, affecting both navigation and drainage, and increases siltation and flooding. Moreover, water hyacinth can block sunlight and provoke oxygen from the fishes, leading to fish kills. Oxygen supply decreases as they compete with other plants and fishes for space in the water.
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2022
Keywords: 2 -- 0; 6; 20; 20; 2